2007
DOI: 10.1111/j.1365-2966.2007.12360.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure and clumping in the fast wind of NGC 6543

Abstract: Far‐ultraviolet spectroscopy from the FUSE satellite is analysed to uniquely probe spatial structure and clumping in the fast wind of the central star of the H‐rich planetary nebula NGC 6543 (HD 164963). Time‐series data of the unsaturated P vλλ1118, 1128 resonance line P Cygni profiles provide a very sensitive diagnostic of variable wind conditions in the outflow. We report on the discovery of episodic and recurrent optical depth enhancements in the P v absorption troughs, with some evidence for a ∼0.17‐d mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 44 publications
(64 reference statements)
1
31
0
Order By: Relevance
“…Ions with higher ionization potential tend to have P Cyg lines with a more extended blue wing. In addition, Prinja et al (2007) showed that the wind variability is present in the absorbtion component of the P v k1118/k1128 doublet but that O vi k1032/k1038 is more stable. The formation of the strong P Cyg lines is obviously complicated, and there is no easy explanation for their behavior.…”
Section: Stellar Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Ions with higher ionization potential tend to have P Cyg lines with a more extended blue wing. In addition, Prinja et al (2007) showed that the wind variability is present in the absorbtion component of the P v k1118/k1128 doublet but that O vi k1032/k1038 is more stable. The formation of the strong P Cyg lines is obviously complicated, and there is no easy explanation for their behavior.…”
Section: Stellar Parametersmentioning
confidence: 99%
“…A detailed analysis of the spectral variability was published by Prinja et al (2007). They found that ''Mostly the flux changes are at $10%Y20% of the continuum level and occur over localized blueward velocity regions, as opposed to the flux increasing or decreasing simultaneously over the entire absorption trough.''…”
Section: Modelmentioning
confidence: 99%
“…The red component of the doublet is usually blended with the Si iv λ1128.3 line, and thus we have focused on the blue component. The P Cygni profiles of unsaturated P v λ1118, 1128 lines have been singled out as a sensitive diagnostic of variable conditions in the wind of CSPNe (Prinja et al 2007). …”
Section: Atlas Of Fuse P-cygni Profiles Of Cspnementioning
confidence: 99%
“…When necessary, we adopted the Notes. (a) The FUSE spectra of Hen 2-138 and NGC 6543 have been thoroughly investigated by Prinja et al (2007Prinja et al ( , 2010 and will not be discussed in the following sections.…”
Section: Near-uv Datamentioning
confidence: 99%
See 1 more Smart Citation